PENGARUH LIKUIDITAS, RISIKO BISNIS, PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN, PAJAK DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2015-2017 - Nadi Tri Saputro, 15.05.52.0276; Irsad, Moch (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of liquidity, business risk, sales growth, company size, tax and profitability on the capital structure of manufacturing companies listed on the Indonesia stock exchange for the period 2015-2017. The population in this study are all Manufacturing Companies Registered on the Stock Exchange of the 2015-2017 Period. The sample selection uses the purpose sampling method. The analytical tool used in this study is multiple linear regression analysis. The test results show that liquidity has a significant negative effect on capital structure. business risk and sales growth have a significant positive effect on the capital structure. While the size of the company has a positive and insignificant effect on the capital structure. While tax and profitability have no significant negative effect on capital structure.